Assessment of Duration and Frequency of Drought by Percent Normal Precipitation Index (PNPI) for Lombok Island - Humairo Saidah; Muh. Bagus Budianto; I Wayan Yasa; Syamsul Hidayat; I Dewa Gede Jaya Negara; Heri Sulistiyono (Journal of Science and Science Education, 2022)
Meteorological drought is a climatic condition categorized by a scarcity of rainfall. Understanding the drought characteristics is a significant step appointed uncertain climate conditions due to current global climate change. This study aims to assess the duration and frequency of drought using the Normal Precipitation Index (PNPI) method to identify drought characteristics in the study area. The PNPI revealed a spatial variation in percent value monthly rainfall to average rainfall across the island of Lombok that prolonged and severe droughts have occurred in entire study areas with varying duration and frequency. PNPI method in analyzing drought events in the island of Lombok showed that Sopak is the driest area and Sekotong is the wettest one